Mathematical Model of the Traffic Intensity and of the Quantity of Poisonous Rubbish (On the Example of the Yerevan City) - Ayvazyan, A. (Mathematical Problems of Computer Science, 2021)
In this paper one of the most important problems of the Yerevan City are considered that is organising automobile transport traffic with purpose of control and calculation of street’s traffic intensity and quantity of poisonous rubbish in the result of it. The space picture of the Yerevan City is taken as initial data. The corresponding database is created and automatic system is developed in virtue of which the specialized map of the Yerevan City transport streams loading can be formed.